THE EFFECT OF WORKLOAD AND SELF-EFFICACY ON CYBERLOAFING BEHAVIOR ON EMPLOYEE PERFORMANCE AT PURWOKERTO ISLAMIC HOSPITAL - Gamasiwi, Ratu Janisa; Salsabil, Azzah Sukma; Novarizka, Shalsabilla; Putri, Tri Iriani; Ikhsani, Mastur Mujib (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to determine and analyze the effect of workload and self-efficacy on cyberloafing behavior on the performance of employees at the Purwokerto Islamic Hospital. Sampling using incidental sampling method through a questionnaire. The sample used was 154 employees. Researchers conducted data analysis using the Partial Least Square (PLS) method using SmartPLS software. The results of this study indicate that workload, self-efficacy, and cyberloafing behavior have a positive and significant effect on employee performance partially; Workload and self-efficacy have a positive and significant impact on cyberloafing behavior partially; And workload has a negative and insignificant influence on cyberloafing behavior partially.